Siderophile metal fallout to Greenland from the 1991 winter eruption of Hekla (Iceland) and during the global atmospheric perturbation of Pinatubo - Gabrielli, P; Barbante, C; Plane, J; Boutron, C; Jaffrezo, J; Mather, T; Stenni, B; Gaspari, V; Cozzi, G; Ferrari, C; Cescon, P (2008)
Ir and Pt are siderophile elements that are considered proxies of meteoric material of cosmic origin entrapped within polar ice layers. However, volcanic and anthropogenic fallouts have the potential to perturb their characteristic extraterrestrial signature even in remote polar areas. Here we show a record of Ir and Pt concentrations in snow samples collected from a 2.7 m pit, which was dug at Summit (Central Greenland), and covered five years from winter 1991 to summer 1995. A well-defined peak of Pt, and a spike of Ir, were found at the base of the snow pit record. These maxima occur in close concurrence with large concentration peaks in Al, Ag, Cd and Hg. Dating of the snow layers together with some geochemical evidence suggests that these peaks originated from the fallout to Greenland of volcanic ash emitted by the nearby Hekla volcano (Iceland), during the eruption of January-March 1991. Interestingly, an anomalous peak of methane sulfonic acid (MSA) in Greenland snow also corresponds to the Hekla ash fallout. This might point to an early biomass production in the North Atlantic Ocean during the first half of 1991, which was possibly stimulated by the fertilizing action of the Hekla ash fallout to seawater. During the following years (1992-1995) the global atmosphere was under the influence of the large perturbation produced by the eruption of Mt. Pinatubo (Philippines) in June 1991. Relatively high Ir and Pt concentrations with super-chondritic ratios are recorded especially during summer 1993. We discuss if this can be interpreted as the possible stratospheric input of Pinatubo's aerosol or fallout of extraterrestrial origin. During the same period the snow pit record was also influenced by the advection of air masses enriched in Pt with respect to Ir. One possibility is that this additional Pt contribution originated from widespread emissions into the troposphere produced by vehicles equipped with catalytic converters. In any case, Pt concentration levels found in recent Greenland snow are about two orders of magnitude lower than previously thought, pointing to a much lower anthropogenic contamination of the Arctic regions from Pt. This challenges the concept of an important hemispheric contamination of Pt from vehicles equipped with catalytic converters. © 2008.